Mutations in the KIF21B kinesin gene cause neurodevelopmental disorders through imbalanced canonical motor activity - Laure Asselin (Nature Portfolio, 2020)
Kinesins regulate intracellular transport and microtubule dynamics. Here, the authors show that KIF21B variants in humans associate with corpus callosum agenesis and microcephaly. Using mice and zebrafish, they showed the cellular mechanisms altered by the missense KIF21B variants.